LEARNING FROM THE SUCCESS OF CHARACTER EDUCATION MODEL IN MUHAMMADIYAH SCHOOLS: Case Study SMP Muhammadiyah PK Kottabarat Surakarta and SMP Birul Walidain Muhammadiyah Sragen - Mohamad ali; Ana Retna (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
The essence of education is the inculcation and reinforcement of good characters instead of merely generating professionals. Various efforts have been made to strengthen the character of the nation. A series of regulations have been issued to promote the strengthening of national character, including Permendikbud No. 23 of 2017 on School Days and Perpres No. 87 of 2018 on Strengthening Character Education, due to the concern of the infiltration of hedonism and pragmatism. Schools become the primary institution to promote character strengthening movements. Nevertheless, the character education program in schools is deemed to be less optimal due to the implementation of partial and fragmented approaches. The success of the two Muhammadiyah schools, namely SMP Muhammadiyah PK Kottabarat Surakarta and SMP Birul Walidain Muhammadiyah Sragen, in carrying out character education with a holistic approach is examined and discussed as a reference for other schools.